2019
DOI: 10.1111/jam.14208
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the bacterial viability of chlorine‐ and quaternary ammonium compounds‐treated Lactobacillus cells via a multi‐method approach

Abstract: Aims: The assessment of the bacterial viability of chlorine-and quaternary ammonium compounds (QACs)-treated Lactobacillus cells by culture-dependent and -independent methods. Methods and Results: Lactobacillus isolates (Lactobacillus plantarum G1, Lactobacillus plantarum B1, Lactobacillus brevis S1 and Lactobacillus paracasei W1) in biofilm and planktonic cell suspensions were treated with chlorine-based (0Á018 and 0Á18%) and QACs-based (0Á2 and 2Á0%) disinfectants for 5 min and then analysed by plate countin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Previous studies have shown how various food spoilage and pathogenic bacteria can persist due to biofilm formation either on food or in a food production environment, e.g., Escherichia coli O157:H7 [13], Salmonella enteritidis [5], Listeria monocytogenes [14], Pseudomonas aeruginosa [15], Pseudomonas fragi [16], Bacillus cereus [17], and Lactobacillus plantarum [18,19]. It is thus very difficult to control these bacteria within biofilms, despite applying the best antimicrobial agents [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown how various food spoilage and pathogenic bacteria can persist due to biofilm formation either on food or in a food production environment, e.g., Escherichia coli O157:H7 [13], Salmonella enteritidis [5], Listeria monocytogenes [14], Pseudomonas aeruginosa [15], Pseudomonas fragi [16], Bacillus cereus [17], and Lactobacillus plantarum [18,19]. It is thus very difficult to control these bacteria within biofilms, despite applying the best antimicrobial agents [20].…”
Section: Introductionmentioning
confidence: 99%
“…As cells imposing injury state (Syto ® 9 + PI + ) have already been characterised (Ben‐Amor et al ., ; Berney et al ., ), the phenomenon of Syto ® 9 − PI − cells is not well‐understood. This study show that Syto ® 9 − PI − cells represent an intermediate state with viability reduced to the level dependent on the bacterial cells and conditions applied, which concurs with previous work performed by our group (Olszewska et al ., ). As shown for L. plantarum B1, the ability of Syto ® 9 − PI − cells to grow on agar plates was largely lost by planktonic cells but not by biofilm ones after AA treatment.…”
Section: Overall Discussionmentioning
confidence: 98%
“…Optical filters were set up so that the red fluorescence was measured above 670 nm (FL4) and the green fluorescence was measured at 520 nm (FL1). Two independent trials of suspended cells were sorted with the same instrument (Beckman Coulter), as described elsewhere (Olszewska et al, 2019).…”
Section: Flow Cytometric Measurements and Cell Sortingmentioning
confidence: 99%
See 2 more Smart Citations